Growth Differentiation Factor-15 (GDF-15) Is Associated With Mortality in Ischemic Stroke Patients Treated With Acute Revascularization Therapy - Brenière, Céline; Méloux, Alexandre; Pédard, Martin; Marie, Christine; Thouant, Pierre; Vergely, Catherine; Béjot, Yannick (Frontiers in Neurology, 2019)
Background and Aims – Growth differentiation factor-15 (GDF-15) has been identified as a robust marker of developing cardiovascular disease, however, little is currently known about its prognostic value in stroke patients. In a context of growing interest to discover new biomarkers in stroke, we aimed to assess the association between circulating GDF-15 levels and three-month mortality in ischemic stroke patients treated with acute revascularization therapy. Methods – 173 patients hospitalized for acute ischemic stroke and treated with either intravenous thrombolysis (n=99, 57.2%), mechanical thrombectomy (n=41, 23.4%) or combined therapy (n=33, 19.1%) were prospectively included. Baseline clinical and biological characteristics were recorded. Plasma GDF-15 levels were measured at admission (D0), and at 24 hours, 3 days and 7 days. Clinical severity was assessed with the National Institutes of Health Stroke Scale score, and vital status was obtained three months after the stroke. Results - At 3 months post-stroke, 32 patients (18.5%) had died. The deceased patients had higher D0 plasma GDF-15 levels (median [IQR]: 2,777 [1,769-5,446] versus 1,460 [965-2,079] pg/mL, P<0.001). In multivariable logistic regression analysis, D0 GDF-15 levels in the third tertile of the distribution were independently associated with mortality at 3 months (OR=3.71; 95% CI: 1.09-12.6, P=0.036), even after adjustment for confounding variables including clinical severity. Conclusions – Our data show for the first time that GDF-15 plasma concentration at admission is independently associated with three-month mortality in ischemic stroke patients treated with acute revascularization therapy. The pathophysiological mechanisms that could explain this association warrant further study.